Strategy Campaign Party Justice Prosperous To Capture Victory In Election 2024 (Studies Case Election Legislative In Level Dprd Dki 2024) - Mulyani, Mega Tiara; Ummah, Aniqotul (UNIVERSITAS PAKUAN, 2025)
This journal will analyze the campaign strategy of the Prosperous Justice Party (PKS) in winning the 2024 Election, specifically in election legislative at the DPRD level Jakarta. This research review through descriptive qualitative research methods explores how PKS designs effective campaign strategies to increase electability amidst increasingly tight political competition. This study uses an interview approach to sources directly involved in the campaign as well as relevant literature studies. PKS campaign strategy analyzed using campaign theory from Venus (2004) which share campaign into four types, with Research result show that success PKS in increase vote acquisition in DPRD DKI Jakarta in 2024 cannot be separated from a structured and adaptive campaign strategy, by prioritizing Islamic values, justice social, And approach direct to voters. Image strengthening party through social media, social activities, and face-to-face communication successfully create emotional closeness with constituents. This research confirms the importance of consistent and value-based political communication strategies in building voter trust and loyalty towards the party political.